Communication Networks in Event Planning - Forsberg, Cierra; Lochner, Angela; Markham, Mallory; Williams, Brittany (My University, 2010)
The purpose of this study is to investigate the role of informal communication in forming organizational networks, in the context of event planning. This industry involves coordination throughout planning and is a platform to study inter-organizational networks. Networks play a vital role in providing additional resources, stability and efficient work. Our research aims to understand the role of communication in networks while planning an event.
Color poster with text and tables.
Keywords: Communication in organizations; Communication--Network analysis; Special events--Planning; Posters